2022
DOI: 10.18087/cardio.2022.9.n2037
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of non-traditional lipid parameters: Castelli Risk Index I, Castelli Risk Index II, and triglycerides to high-density lipoprotein cholesterol ratio among patients with non-ST-segment elevation myocardial infarction during 1‑year follow-up

Abstract: Aim    Concentrations of classical lipoproteines have a well-established role in non-invasive cardiology. The efficacy of the Castelli Risk Index I (CRI I), Castelli Risk Index II (CRI II), and triglycerides to high-density lipoprotein cholesterol (TG / HDL-C) ratio in clinical practice are currently under evaluation. The study aimed to assess the predictive value of CRI I, CRI II and TG / HDL-C for the incidence of Major Adverse Cardiovascular Events (MACE) and for all-cause mortality during 1‑year follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Although these findings support that CRI can be an important screening tool in predicting CAD, there are studies reporting the opposite. In a study conducted with non-ST-segment elevation myocardial infarction patients, it was reported that there was a low correlation between CAD severity and CRI-I, but CRI-II did not show a significant relationship [19]. On the other hand, previous studies have reported a positive correlation between the myocardial damage and extent of CAD [20][21][22].…”
Section: Discussionmentioning
confidence: 94%
“…Although these findings support that CRI can be an important screening tool in predicting CAD, there are studies reporting the opposite. In a study conducted with non-ST-segment elevation myocardial infarction patients, it was reported that there was a low correlation between CAD severity and CRI-I, but CRI-II did not show a significant relationship [19]. On the other hand, previous studies have reported a positive correlation between the myocardial damage and extent of CAD [20][21][22].…”
Section: Discussionmentioning
confidence: 94%
“…CRI I and CRI II were initially proposed by Castelli and colleagues as strong predictors of coronary artery disease 53 . Both Castelli indices showed statistical significance for predicting peripheral arterial disease, intracranial atherosclerotic stenosis, and cardiovascular risk in men 14 . CRI I reflects the formation of coronary plaques with a diagnostic value as good as the determination of total cholesterol and is consistently associated with arterial stiffness in a range of LDL‐C levels, even if LDL‐C is below 70 mg/dL 54 .…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] However, it has been argued that reliance on LDL-C or HDL-C alone is not adequate and the combination of multiple lipid parameters and unconventional lipid indices is a more reliable and accurate risk than simple lipid parameters in disease prediction, especially when the conventional lipid parameters are apparently normal or moderately high. 10,11 These unconventional lipid ratios, which are called atherosclerosis indices, include: atherogenic coefficient (AC), Castelli's risk index I (CRI I) and II (CRI II), atherogenic index of plasma (AIP), and non-HDL-C. 10,[12][13][14] The triglyceride-glucose (TyG) index, fasting blood glucose (FBG) and triglyceride synthesis parameter has been proposed as an important risk marker to evaluate insulin resistance and CVD risk. 15 According to reports, insulin resistance is implicated in the pathogenic processes of arterial hypertension by its effect on endothelial function, renal sodium metabolism, sympathetic nerve system activation, and modulation of vasoactive substances secretion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations